The Impact of Sharia Securities Crowdfunding on The Performance of The Islamic Capital Market in Indonesia: A Conceptual Review of Strengthening The Islamic Financial Ecosystem - Masruri Masruri; Ahmad Solekhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of financial technology has accelerated the development of Sharia Securities Crowdfunding (SSCF) as an innovative financing and investment mechanism within Indonesia's Islamic financial ecosystem. This study aims to conceptually examine the impact of SSCF on the performance of the Islamic capital market through a qualitative approach employing library research integrated with a Systematic Literature Review (SLR). The analysis synthesizes evidence from academic publications, regulatory documents, and institutional reports to evaluate the strategic role of SSCF from the perspectives of Financial Intermediation Theory, Financial Inclusion Theory, and Signaling Theory. The findings indicate that SSCF strengthens the Islamic capital market by improving financial intermediation, expanding financing access for Micro, Small, and Medium Enterprises (MSMEs), broadening investor participation, and enhancing market transparency through Sharia-compliant digital platforms. Nevertheless, its sustainable development remains constrained by regulatory adaptation, governance quality, financial literacy, cybersecurity, and stakeholder coordination. Strengthening regulatory harmonization, institutional collaboration, digital infrastructure, and Islamic financial literacy is therefore essential to maximize the contribution of SSCF to a resilient, inclusive, and sustainable Islamic financial ecosystem in Indonesia.